Oil Price and Fijian Tourism Cycle: A Markov Regime-switching Model - Soh, Ann-Ni; Puah, Chin-Hong; Arip, M. Affendy; Kuek, Tai-Hock (International Journal of Energy Economics and Policy, 2019)
The fluctuation of oil price tends to have adverse effect on the tourism industry of a nation. This paper investigates the dynamic changes of the inbound tourism market for Fiji and the driving forces of the Fijian tourism cycle. A set of fundamental determinants of tourism demand including international crude oil price has been utilized to predict the Fijian tourism cycle for the period of 2000-2017. The Markov regime-switching model identifies two distinct phases of the Fijian tourism cycle which are an expansion and a recession period. The filtered and smoothed probabilities signalled the Fijian tourism development significantly with the transition probabilities supported. The adequate dating evaluation can offer essential information for policymakers, tourism industry players and even the community in decision making for Fijian tourism to enhance the nation's development. Keywords: Markov-switching model, Fijian tourism cycle, Oil price fluctuation, Forecasting JEL Classifications: Z32; O01; E32 DOI: https://doi.org/10.32479/ijeep.8087